№1. Решите неполное квадратное уравнение:
1) 6х2 - 3х = 0; 3) х2 – 36 = 0; 5) 0,5х2 – 1 = 0;
2) х2 + 9х = 0; 4) 5х2 + 1 = 0; 6) 0,6х + 9х2 = 0.
№2. Решите квадратное уравнение:
1) х2 + 7х + 12 = 0; 3) 2х2 - 5х – 3 = 0;
2) х2 – 2х – 35 = 0; 4) 3х2 – 8х + 3 = 0.
du/dx=3x²y³(tg²(x³y³)+1)
d²u/dx²=6xy³(tg²(x³y³)+1)+3x²y³2(tg(x³y³)3x²y³(tg²(x³y³)+1)==6xy³(3x³y³tg(x³y³)+1)(tg²(x³y³)+1)
Аналогично
du/dy=3x3y2(tg²(x³y³)+1)
d²u/dy²=6x³y(tg²(x³y³)+1)+3x³y²2(tg(x³y³)3x³y²(tg²(x³y³)+1)==6x³y²(3x³y³tg(x³y³)+1)(tg²(x³y³)+1)
смешанные
d²u/dxdy=d(3x²y³(tg²(x³y³)+1))/dy=9x²y²(tg²(x³y³)+1)+3x²y³2tg(x³y³)3x³y²(tg²(x³y³)+1)=9x²y²(2x³y³tg(x³y³)+1)(tg²(x³y³)+1)
d²u/dydx=d(3x³y²(tg²(x³y³)+1))/dx=9x²y²(tg²(x³y³)+1)+3x³y²2tg(x³y³)3x²y³(tg²(x³y³)+1)=9x²y²(2x³y³tg(x³y³)+1)(tg²(x³y³)+1),
т.е. смешанные производные равны